2019
DOI: 10.3389/fgene.2019.00825
|View full text |Cite
|
Sign up to set email alerts
|

CeRNA Expression Profiling Identifies KIT-Related circRNA-miRNA-mRNA Networks in Gastrointestinal Stromal Tumour

Abstract: Gastrointestinal stromal tumours (GISTs) are the most common human sarcomas and are typically located in the stomach or small intestine. Although circular RNAs (circRNAs) reportedly play vital roles in tumour oncogenesis and progression, the molecular basis of the aggressive tumour biology of these circRNAs in GISTs remains unclear. In this study, we applied SBC ceRNA microarrays to screen for tumour-specific circRNA profiles in GISTs and identified that a total of 5,770 circRNAs and 1,815 mRNAs were different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…CircRNAs belong to a family of endogenous ncRNAs without 5′ caps or 3′ tails, which have been implicated in inflammation and immune regulation. Apart from interacting with molecules with biological activity directly, a number of circRNAs have also been confirmed to function as ceRNA in cancer, inflammation-related, or autoimmune diseases 25 – 27 . Although several published studies have identified the specific profile of circRNAs in peripheral blood cells of RA patients, whether those circRNAs can function as ceRNA for the dysregulated miRNAs in RA is not clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs belong to a family of endogenous ncRNAs without 5′ caps or 3′ tails, which have been implicated in inflammation and immune regulation. Apart from interacting with molecules with biological activity directly, a number of circRNAs have also been confirmed to function as ceRNA in cancer, inflammation-related, or autoimmune diseases 25 – 27 . Although several published studies have identified the specific profile of circRNAs in peripheral blood cells of RA patients, whether those circRNAs can function as ceRNA for the dysregulated miRNAs in RA is not clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA circ-CPA4 (hsa_circ_0082374) had recently been identified as an oncogene in glioma [ 34 ], however, little known about the role of this circRNA in regulating progression of other types of cancer. Besides, circRNAs were known as “sponges” for miRNAs, and circRNAs regulated the levels of their downstream miRNAs in a competing endogenous RNA (ceRNA) dependent manner [ 35 37 ]. In particular, let-7 miRNA could be sponged and inhibited by circ-CPA4 in the development of glioma [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA-miRNA-mRNA network is a widely recognized mode of action in cancer progression [31]. We deduced that circ_0086720 also functioned as a competing endogenous RNA (ceRNA) by targeting downstream miRNAs.…”
Section: Discussionmentioning
confidence: 99%